Synthesis and Application of Cuprous oxide-Potassium Lithium Titanate Composites in the Photocatalytic Degradation of Rhodamine 6G - Baoulan, Areebhorn (Asian Health, Science and Technology Reports, 2020)
The cuprous oxide-potassium lithium titanate composites were prepared by a conventional solid-liquid reaction between potassium lithium titanate (KTLO) and copper acetate subsequent precipitation with sodium hydroxide and glucose. The cuprous oxide-potassium lithium titanate composites were characterized by X-ray diffraction (XRD), Fourier transforms infrared (FT-IR) spectroscopy and UV-Vis diffuse reflectance spectroscopy (DRS). The photocatalytic activity of the cuprous oxide-potassium lithium titanate composites with different cuprous oxide and potassium lithium titanate loading was evaluated in the photocatalytic degradation of rhodamine 6G under visible light irradiation. The composite which containing lower loading amount of cuprous oxide than potassium lithium titanate showed 82% of photodegradation of rhodamine 6G. The cuprous oxide-potassium lithium titanate composite is eco-friendly material with the performance as photocatalysts under solar light.